SIFAT PEMESINAN 34 JENIS KAYU DARI MALUKU & SULAWESI TENGAH - Osly Rachman; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1985)
The machining properties of  34 wood  species  tested according to the ASTMD 1666-64  procedure are presented in this paper.  The machining  properties studied  were planing,  shaping,  turning,  sanding,  boring and  mortising.Some of  the species  tested  (such as suling, gohimahou etc.)  are consistently better  than average in most  respects  and some  are consistently poorer  (such as telor, andolia etc.).  Some  are good  in one property or two and poor in others.  These differences are probably due to differences in the specific gravity  values of  each species